Pemanfaatan Posdaya Masjid Baitussalam sebagai Pusat Pengolahan Sari Buah Markisa di Dusun Robyong, Desa Wonomulyo, Kabupaten Malang - Ari Kusumastuti; Heni Widayani; Angga Dwi Mulyanto; Hisyam Fahmi (Institut Pertanian Bogor, 2019)
The formation of the family empowerment post (Posdaya) at Robyong Sub-village of Poncokusumo is intended to increase family income through the application of technology to utilize existing natural potential endowment. The mosque-based family empowerment post could functionalize mosque as a social-economic community center as well as a religious activity center. The community empowerment program at Baitussalam-Mosque Posdaya has become a pilot project in the mosque-based society empowerment. The implementation of the program consisted of family data collection, socialization, and determination of the Posdaya main program according to local potential. Discussion with locals has concluded that the need for training about passion fruit (Passiflora edulis) processing as a main program of Posdaya, since passion fruit has become potential and not yet being utilized optimally. Participants are locals around Baitussalam Mosque, especially housewives. Direct observation shows that locals actively participate in the Posdaya program and supported also by Posdaya organizer and community leaders. The resulting product was responded positively by the market. The product was already marketed out of Java as a souvenir from the Robyong sub-village of Poncokusumo. This program is expected to become a micro-group enterprise from Robyong sub-village with product diversification, good marketing strategy, and good production management in the future.